Contextualized education in the teaching of Mathematics: a case study at the Kindergarten and Elementary School Manoel Rodrigues do Nascimento (Research, Society and Development, 2020)
Teaching mathematics as a concept formation process requires rethinking the teacher's role, the conditions for organizing pedagogical work, the way of thinking, feeling and acting in education, the characteristics and interests of students. It needs the entire school community's involvement, presenting the content in a contextualized way, through a problematic situation, compatible with a real situation, which has elements that give meaning and construction to the mathematical content. This work sought to broaden the understanding of contextualization in the teaching of mathematics since working with content that is not related to the context in which the student is inserted is not attractive. To this end, a survey was conducted based on a semi-structured interview with the teachers and students of that school, in addition to observations and pedagogical practice. According to the results, the teachers' conceptions are identified and perceived, showing that the methodologies used by them in a contextualized way provide meaningful learning, since teaching is an active, evolving process about contextualization and its contribution to the learning of the students of this school, the research also shows how the contextualized teaching of mathematics is evaluated and the importance of bringing innovative, motivating and meaningful situations to classrooms. Therefore, it is understood that Contextualized Education in the teaching of mathematics enables the construction of the student's knowledge according to his reality, mainly due to the applicability of Mathematics, stimulates creativity, investigation, critical analysis of results and contributes significantly to the teaching-learning process.